Can Smart Electrochemical Sensors Sustainably Tackle PFAS-@Microplastics? - Andrea Lee; Riley Orr; Justin Sanchez-Almirola; Jasmina Casals-Terré; Ajeet Kaushik (ECS Sensors Plus)
Microplastics (MPs, long-lasting pollutants) can carry per- and polyfluoroalkyl substances (PFAS, forever chemicals) in aquatic systems. PFAS@MP complexation is a threat to the human cycle, and tackling this issue is crucial for sustainability. Electrochemical sensors detect MPs (ppb) and PFAS (ppt) selectively, but simultaneous detection of both in the PFAS@MP complexation has not been demonstrated. To handle these issues, the internet-of-things-based sensing technology should be tuned to perform MPs/PFAS sensing at point-of-care applications. Furthermore, incorporating artificial intelligence (AI)-based modeling can aid in risk assessments and decision-making to facilitate efficient management and monitoring of a sustainable environment.